INVASIVE WEEDS IN BOGOR BOTANIC GARDENS, INDONESIA AND ITS IMPLICATION ON SURROUNDING LANDSCAPES - Santosa, Edi; Widiyanto, Gunar; Lontoh, Adolf Pieter; Agustin, Elly Kristiati; Takahata, Ken; Mine, Yoko; Sugiyama, Nobuo (Buletin Kebun Raya, 2014)
Conservation areas with the objective for collection and exchange plant materials have been speculated as weed bank for surrounding areas. Objective of this study was to identify and characterize ruderal invasive weeds in the Bogor Botanic Gardens (BBG). Observations were conducted in all vak (collection blocks) in the BBG in order to identify the weeds species, determine their invasiveness, dominance and distribution. Weeds associations with host plants were observed. Current weed control program and data of dead trees collection were analyzed in relevant to weed. Distribution of weeds outside BBG was observed by transects method following river and road directions. Results showed that there were seven invasive weeds, i.e., Cecropia adenopus (Cecropiaceae), Cissus nodosa Blume (Vitaceae), Cissus sicyoides Blume (Vitaceae), Dioscorea bulbifera L. (Dioscoreaceae), Ficus elastica Roxb. (Moraceae), Mikania micrantha H.B.K. (Asteraceae) and Paraserianthes falcataria (L.) Nielsen (Fabaceae). These seven weeds species invaded 41 out of 215 plant families in BBG. Six species of weeds, i.e., C. adenopus, C. nodosa Blume., C. sicyoides Blume., D. bulbifera L., M. micrantha H.B.K. and P. falcataria (L.) Nielsen, were introduced as BBG collections for the first time while the F. elastica Roxb was considered as native. It is most likely that the weeds dispersal agents are the wind, birds, bats, visitors, and waters. All of these weeds existed in surrounding areas outside BBG. Given the detrimental impact of invasive weeds on the plant collection in BBG, it is necessary to develop longâterm comprehensive control measures both inside and neighboring areas by involving other government authorities beyond BBG.